Tolaram contributes $600,000 to support innovation and entrepreneurship at SMU - Singapore Management University (Institutional Knowledge at Singapore Management University, 2022)
Tolaram, a Singapore conglomerate with businesses in consumer goods, fintech, infrastructure and industrials, has established the Tolaram Innovation and Entrepreneurship Fund at the Singapore Management University (SMU) with a term contribution of S$600,000.